2001
DOI: 10.1054/bjoc.2000.1527
|View full text |Cite
|
Sign up to set email alerts
|

A prospective seroepidemiological study of human herpesvirus-8 infection and the risk of multiple myeloma

Abstract: Presence of the Human Herpesvirus 8 (HHV8) genome has been reported in the bone marrow of multiple myeloma (MM) patients. So far, serological studies of HHV8 and MM have been inconsistent but have not included prospective epidemiological studies. We evaluated whether HHV8 infection is associated with increased risk for MM in a prospective population-based study of 39 000 Finnish subjects who donated serum samples in the period 1968–72. Serum samples from 47 subjects who developed MM during a 23-year follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…KS is a tumour of endothelial cell origin and MCD is a B-cell lymphoproliferative disorder. Recent reports further suggest that KSHV infection might play a role indirectly in the pathogenesis of multiple myeloma [5][6][7]. Like other gammaherpesvirus such as human B lymphocyte-tropic Epstein-Barr virus (EBV), monkey T lymphocyte-tropic herpesvirus saimiri and murine B lymphocyte-tropic herpesvirus 68, KSHV is another human lymphocyte-tropic virus and usually infects B lymphocytes and establishes latency in the lymphocytes following primary infection.…”
Section: Introductionmentioning
confidence: 99%
“…KS is a tumour of endothelial cell origin and MCD is a B-cell lymphoproliferative disorder. Recent reports further suggest that KSHV infection might play a role indirectly in the pathogenesis of multiple myeloma [5][6][7]. Like other gammaherpesvirus such as human B lymphocyte-tropic Epstein-Barr virus (EBV), monkey T lymphocyte-tropic herpesvirus saimiri and murine B lymphocyte-tropic herpesvirus 68, KSHV is another human lymphocyte-tropic virus and usually infects B lymphocytes and establishes latency in the lymphocytes following primary infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is not accurate report for prevalence and incidence of disease in Iran but according to Iranian annual cancer registrant report in 2003, hematopoietic malignancies were the seventh common cancer [19]. It has been suggested that some viruses such as human immunodeficiency virus, hepatitis C virus, Epstein-Barr virus (EBV) and HHV-8 can be contributed in myeloma pathogenesis [5,[20][21][22] but these association has not been completely confirmed [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the latent assay is usually not more than 80-95% [Chatlynne and Ablashi, 1999], while the immunofluorescence assay on virus producing PEL cell lines (''lytic IFA'') has been found to have a sensitivity approaching 100% [Lennette et al, 1996;Smith et al, 1997;Chatlynne et al, 1998;Tedeschi et al, 2001a]. While sensitivity is straightforward to estimate using samples from patients with HHV8-associated disease and/or detectable HHV8 DNA, estimation of specificity is a more challenging issue because it is not possible to exclude that healthy subjects may have or had an HHV8 infection.…”
Section: Discussionmentioning
confidence: 99%